Mapping the margins: Intersectionality, identity politics, and violence against women of color - Crenshaw, Kimberlé William (Stanford Law Review, 1991)
Contemporary feminist and antiracist discourses have failed to consider the intersections of racism and patriarchy. To overcome this difficulty, an original approach is suggested here: that of intersectionality. In the first part, the paper discusses structural intersectionality, the ways in which the location of women of color at the intersection of race and gender makes their real experience of domestic violence, rape, and remedial reform qualitatively different from that of white women. The focus is shifted in the second part to political intersectionality, with the analysis of how both feminist and antiracist politics have functioned in tandem to marginalize the issue of violence against women of color. Finally, the implications of the intersectional approach are addressed within the broader scope of contemporary identity politics.
Keywords: OFDIG; afro-féminisme; antiracisme; approches et analyses; femmes* afro-américaines; féminismes noirs; incontournable; intersectionnalité; militance; patriarcat; ressource en ligne; régions géographiques; systèmes d'oppression; thématiques; violences; violences raciales

Démarginaliser l’intersection de la race et du sexe : une critique féministe noire du droit antidiscriminatoire, de la théorie féministe et des politiques de l’antiracisme - Crenshaw, Kimberlé W. (Droit et société, 2021)
Dans cet article fondateur, K. Crenshaw introduit le concept d’« intersectionnalité », pour penser le caractère composé des effets de subordination liés à des facteurs comme la race, le genre, l’âge, la sexualité, etc. Elle analyse d’abord trois affaires juridiques qui ont traité des questions de discrimination raciale et sexuelle pour montrer les limites des « analyses à enjeu unique » : DeGraffenreid v. General Motors, Moore v. Hughes Helicopter, Inc. et Payne v. Travenol. Dans aucune de ces affaires, les tribunaux n’ont permis aux plaignantes d’alléguer une discrimination fondée à la fois sur la race et le sexe. K. Crenshaw montre qu’il faut penser l’intersectionnalité des discriminations pour saisir et corriger la situation particulière des femmes noires. Dans un second temps, elle élargit la réflexion vers le cadre sociopolitique et suggère que la condition des femmes noires doit être mieux prise en compte tant par les mouvements féministes que par les mouvements anti-racistes.
Keywords: amériques; antiracisme; approches et analyses; discipline; droit; fem1000; incontournable; intersectionnalité; militance; premier cycle; régions géographiques; systèmes d'oppression; thématiques; violences; états-unis